Amplification of genomic DNA demonstrates the presence of the t(2;5)(p23;q35) in anaplastic large cell lymphoma, but not in other non- Hodgkin's lymphomas, Hodgkin's disease, or lymphomatoid papulosis - A.H. Sarris; Luthra, R.; Papadimitracopoulou, V.; Waasdorp, M.; Dimopoulos, M.A.; McBride, J.A.; Cabanillas, F.; Duvic, M.; Deisseroth, A.; Morris, S.W.; Pugh, W.C. (Blood, 1996)
Anaplastic large cell lymphoma (ALCL) is a distinct clinicopathologic variant of intermediate grade non-Hodgkin's lymphomas (NHL) composed of large pleomorphic cells that usually express the CD30 antigen and interleukin (IL)- 2 receptors, and is characterized by frequent cutaneous and extranodal involvement. With variable frequency ALCL bear the t(2;5)(p23;q35) chromosomal translocation that fuses the nucleophosmin (NPM) gene on chromosome 5q35 to a novel protein kinase gene, Anaplastic Lymphoma Kinase (ALK), on chromosome 2p23. We determined the frequency of this translocation with e novel DNA polymerase chain reaction (PCR) technique using 0.5 μg of genomic DNA, 5'-primers derived from the NPM gene and 3'-primers derived from the ALK gene and hybridization with internal probes. The presence of amplifiable DNA in the samples was tested with the inclusion in the PCR reaction of oligonucleotide primers designed to amplify a 3016-bp fragment from the β-globin locus. NMP-ALK fusion amplicons were detected using DNA isolated either from all three ALCL cell lines tested, or from all four primary ALCL tumors known to contain the t(2;5)(p23;q35) translocation. Nested amplicons were detected by hybridization in 100% of specimens diluted 104-fold and in 20% of those diluted 105-fold. We subsequently examined archival genomic DNA from 20 patients with ALCL, 39 with diffuse large cell, 2 with mantle cell, 20 with peripheral T cell, 13 with low-grade NHL, 31 with Hodgkin's disease (HD), and 6 with lymphomatoid papulosis. Fusion of the NPM and ALK genes was detected in three of 18 patients with ALCL who had amplifiable DNA (17%, 95% confidence intervals 4% to 41%), but not in any patients with other NHL, HD, or lymphomatoid papulosis. The amplicon sizes were different in all cell lines and patients reflecting unique genomic DNA breakpoints. We conclude that with genomic DNA-PCR the rearrangement of the NPM and ALK loci is restricted to patients with ALCL. Further studies are needed to determine the prognostic significance of the NPM-ALK rearrangement, to determine whether its detection can aid in the differential diagnosis between ALCL, Hodgkin's disease, and lymphomatoid papulosis, and to establish the usefulness of the genomic DNA PCR in the monitoring of minimal residual disease in those patients whose tumors bear the t(2;5).